Movies in the Age of Obama: The Era of Post-Racial and Neo-Racist Cinema - Izzo, David Garrett (Rowman & Littlefield Publishers, 2014)
The historic election of Barack Obama to the presidency of the United States had a significant impact on both America and the world at large. By voting an African American into the highest office, those who elected Obama did not necessarily look past race, but rather didn’t let race prevent them for casting their ballots in his favor. In addition to reflecting the changing political climate, Obama’s presidency also spurred a cultural shift, notably in music, television, and film. In Movies in the Age of Obama: The Era of Post-Racial and Neo-Racist Cinema, David Garrett Izzo presents a varied collection of essays that examine films produced since the 2008 election. The contributors to these essays comment on a number of films in which race and “otherness” are pivotal elements. In addition to discussing such films as Beasts of the Southern Wild, Black Dynamite, The Blind Side, The Butler, Django Unchained, The Help, and Invictus, this collection also includes essays that probe racial elements in The Great Gatsby, The Hunger Games, and The Mist. The volume concludes with several essays that examine the 2013 Academy Award winner for best picture, 12 Years a Slave. Though Obama’s election may have been the main impetus for a resurgence of black films, this development is a bit more complicated. Moviemakers have long responded to the changing times, so it is inevitable that the Obama presidency would spark an increase in films that comment, either subtly or overtly, on the current cultural climate. By looking at the issue these films address, Movies in the Age of Obama will be of value to film scholars, of course, but also to those interested in other disciplines, including history, politics, and cultural studies.